CHALLENGE AND CHANGE IN SCHOLASTIC JOURNALISM AS RELATED TO THE TEACHING AND LEARNING OF ENGLISH LANGUAGE ARTS - Stacy Haynes-Moore (Soegijapranata Catholic University, 2013)
Changing notions of literacy impact and complicate ways in which English language arts educators adapt curriculum in meaningful ways for students. In this paper, I position scholastic journalism as authentic, 21st It is a wintery Saturday morning and a small group of student writers and editors wait outside Publications Room 70 eager for me to unlock the school door. The group is ready to work. They century ELA coursework. I provide an historical overview of scholastic journalism. I emphasize impacts of media law, emergent technologies, and redesigned school literacy goals to the ways in which scholastic journalism negotiates acceptance within ELA curriculum.